Digital teaching tools in sports medicine: A randomized control trial comparing the effectiveness of virtual seminar and virtual fishbowl teaching method in medical students. - Stefan Hertling; Doreen Hertling; Georg Matziolis; Ekkehard Schleußner; Franziska Loos; Isabel Graul (PLoS ONE, 2022)
Background Since the COVID-19 pandemic, the demand for online courses has increased enormously. Therefore, finding new methods to improve medical education is imperative. Objective The aim of this study was to compare the self-reports of the individual student-centered virtual teaching techniques (seminar versus fishbowl) in a group of medical students. Methods During the second semester of 2020, students in the clinical phase of the study (n = 144) participated in the optional subject of Sports Medicine. The students were divided into 2 groups. One group (n = 72) received the knowledge transfer in the form of a virtual seminar, the other group (n = 72) in the form of a virtual fishbowl. Results Virtual seminar and virtual fishbowl students gave insights into these teaching techniques. Most of the students from the virtual fishbowl group believed that the virtual fishbowl format allowed them to be more actively involved in learning. The mean quiz scores were statistically higher for students in the virtual fishbowl group than students in the virtual seminar group (p < 0. 001). Conclusion This study concluded that virtual seminars and virtual fishbowl formats could be served as structured learning and teaching formats. At the same time, the virtual fishbowl format can promote an active exchange of knowledge from students' perspectives.